Limitations to fluid replacement during exercise - Maughan, R. J.; Leiper, J. B. (Canadian Journal of Applied Physiology, 1999)
Fluid replacement during exercise is essential for endurance exercise performance and reducing the risk of heat illness. Fluids supply water, which ameliorates dehydration, and also substrate for the working muscles. Absorption of water and nutrients occurs in the upper part of the small intestine, and replacement may be limited by the rate at which fluid is emptied from the stomach or absorbed in the intestine. Gastric emptying of liquids is influenced primarily by the volume of fluid in the stomach and by its energy density. Increasing the volume will speed emptying, but increasing the nutrient content will slow emptying. Osmolality, temperature, and pH of drinks, as well as exercise intensity, are of minor importance. Intestinal water absorption is a passive process: water follows osmotic gradients but will also follow the active absorption of nutrients, especially glucose, which is actively co-transported with sodium. Water transport is maximised by the presence in the intestine of hypotonic solutions of glucose and sodium. Hypertonic solutions promote net water secretion into the intestinal lumen, resulting in a temporary net loss of water from the body. The amount of fluid ingested by athletes is normally much less than can be tolerated, therefore issues such as palatability and practising drinking during training are important.